Consecutive evaluation of Euler sums - Khristo N. Boyadzhiev (International Journal of Mathematics and Mathematical Sciences)
We describe a simple method for a consecutive evaluation of the Euler sums S(r,p), r=1,2,… in terms of zeta values.